5 Use of propranolol for infantile haemangiomas: multi-centre experience of 70 cases. (28th April 2017) - Fortner, Rainer; Scheller, Marcia; Wilson, Alexander; Govindaraj, Poonamallee; Ashtekar, Sandeep; Wilson, Dirk
Abstract : Background: Propranolol has been used to treat infantile haemangiomas since 2008. Treatment is recommended in lesions complicated by bleeding, ulceration, infection and where breathing, feeding or vision is compromised. We assessed our experience with reference to the proposed Great Ormond Street protocol (2014) which rationalises pretreatment management/investigations. Methods: Retrospective review of electronic records of all children who receiving propranolol for infantile haemangiomas in 3 hospitals in South Wales between 2009 and 2014. Results: 70 children were treated with propranolol. Median age [range] at start of treatment was 4 months [0-24]. Indications for treatment included ocular impairment (40%), cosmesis (29%), ulceration (21%), airway impairment (6%) and miscellaneous (4%). Median length of treatment was 10 months [1–16]. 88.6% of children improved on treatment and only 5 (7%) experienced regrowth on cessation. 12 patients (17.1)% experienced side effects and 7 (10%) had their treatment discontinued or adjusted. Recorded side effects included sleep disturbance (7%), GI upset (3%) and wheeze (3%). All children were examined by a Paediatrician, Neonatologist or Paediatric Cardiologist prior to treatment initiation. 10 (7%) children were noted to have a murmur. ECG and echocardiography were normal in all but one child who was later found to have an arteriovenous malformation rather than haemangioma, requiring embolisation. Conclusion: None of the investigations including echocardiography and blood tests revealed abnormalities contraindicating the administration of propranolol. The selective use of pre-treatment investigations is therefore supported by our data. This review confirms that propranolol is a safe and effective treatment for infantile haemangiomas.